1995
DOI: 10.1038/jcbfm.1995.50
|View full text |Cite
|
Sign up to set email alerts
|

Local Cerebral Glucose Utilization and Cytoskeletal Proteolysis as Indices of Evolving Focal Ischemic Injury in Core and Penumbra

Abstract: Summary:To ascertain the tempo of progression to irre versible injury in focal ischemia, we subjected halothane anesthetized Sprague-Dawley rats to photochemically in duced distal middle cerebral artery occlusion (dMCAO) combined with permanent ipsilateral and 1 h contralateral common carotid artery occlusions. Head temperature was maintained at 36°C. At times centered at either 1.5 or 3 h post-dMCAO, the rate of local glucose metabolism (lCMRgl) was measured by 2-deoxyglucose autoradiogra phy, and cytoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…However, the major findings that the degree of delayed axotomy correlated with the severity of the initial CBF reduction and flow-metabolism uncoupling and that a threshold relationship exists for this, do tend to support the idea that mismatches in energy supply are a major factor involved in the pathogenesis of progressive axonal injury. A previous study on the ischemic rat brain demonstrated that initially after injury, gray matter cytoskeletal injury was lower and more variable in the hypermetabolic penumbral areas compared to the hypometabolic core (Yao et al, 1995). However, levels were similar at later time points when all regions became hypometabolic, indicating that a period of energy failure is required for irreversible cytoskeletal breakdown.…”
Section: Relationship To Axonal Injurymentioning
confidence: 94%
“…However, the major findings that the degree of delayed axotomy correlated with the severity of the initial CBF reduction and flow-metabolism uncoupling and that a threshold relationship exists for this, do tend to support the idea that mismatches in energy supply are a major factor involved in the pathogenesis of progressive axonal injury. A previous study on the ischemic rat brain demonstrated that initially after injury, gray matter cytoskeletal injury was lower and more variable in the hypermetabolic penumbral areas compared to the hypometabolic core (Yao et al, 1995). However, levels were similar at later time points when all regions became hypometabolic, indicating that a period of energy failure is required for irreversible cytoskeletal breakdown.…”
Section: Relationship To Axonal Injurymentioning
confidence: 94%
“…Previous studies have shown that Ca 2+ -mediated proteolysis of cytoskeletal proteins such as spectrin and MAP-2 occurs during the first few hours after ischemia/reperfusion and correlates closely with subsequent neuronal degeneration and death (29,30,31). Because our data indicated that Ca 2+ influx through N-methyl-D-aspartate NMDA receptors and VDCC is enhanced in neurons lacking gelsolin, we performed immunohistochemical analyses to assess the development of Ca 2+ -mediated proteolysis following MCA occlusion in gsn +/+ and gsn -/-mice.…”
Section: Increased Cytosolic Ca 2+ Concentrations In Cortical Nerve Tmentioning
confidence: 99%
“…21 A silver staining method was chosen since proteolysis of fibrillic macromolecules that are stained by silver starts a few minutes after onset of ischemia. 22,23 For SIS, the slides were submerged for 2 minutes into a silver impregnation solution (see below), which was shaken vigorously. Then the slides were washed in distilled water 6 times for 1 minute before they were transferred to a vigorously shaken developer solution for 3 minutes (see below).…”
Section: Silver Infarct Stainingmentioning
confidence: 99%